The The Relationships Between Facility Service Quality and Quality of Life Levels Among Projek Perumahan Rakyat (PPR) Residents in Subang, Selangor - Nur Alina Natasha Azmi, (Research in Management of Technology and Business, 2023)
In some residential neighbourhoods, facility management can have an impact on residents' quality of life (QoL) by upholding the standard of the facilities offered. In order to ensure that the residents' quality of life is met, it is crucial that management is effective in preserving the facility's quality. Damage to amenities like building elevators in the PPR region has put inhabitants through a lot of hardship and worry and has turned into a significant issue in the residential area, particularly in the PPR housing scheme. The residents' quality of life was impacted by this issue due to PPR's inadequate management in maintaining the standard of facilities offered. In order to determine the facilities' quality in PPR and to analyse how it affects inhabitants' quality of life, a study was done to evaluate the facilities' quality. A total of 93 responses were gathered quantitatively and analysed using descriptive, factor, and regression analysis based on the SERVQUAL component and the quality of life (QoL) component, which are two defined variables. According to the study's findings, some of the PPR's facilities are in excellent shape while others are on the verge of collapse. The findings of this study also revealed that, while one SERVQUAL component had no effect on residents' satisfaction in the study area, the other four SERVQUAL components did.